The effect of 8-week Tai Chi training on emotional regulation in female college students: an ERP study of N2 and P3 under a modified oddball paradigm - Yuan, Jin; Zeng, Quanwen; Feng, Dan; Wang, Yu; Li, Huimin; Cong, Zhengzhou; Xu, Jiamin; Wang, Anjie; Li, Jun; Zhang, Yong (Frontiers in Psychology, 2025)
BackgroundEmotion regulation is vital for psychological well-being. Exercise can enhance regulation via attentional and cognitive control, with event-related potentials (ERPs) offering neural insights. Tai Chi benefits mood and stress, yet its neurophysiological effects remain unclear. This study examined the impact of 8-week Tai Chi training on N2 and P3 components of emotional processing in female college students using a modified oddball paradigm.MethodForty healthy female college students were randomly assigned to an 8-week Tai Chi group (n = 20, 20.25 ± 1.33 yrs.) or control group (n = 20, 19.65 ± 1.09 yrs.). Tai Chi participants completed thrice-weekly 50 min sessions at 60–69% HRmax, including warm-up, practice, and relaxation, while controls observed without exercising. Pre- and post-intervention, all completed a modified oddball task recording N2/P3 ERPs and reaction times, alongside emotional regulation assessments, enabling comparison of neurophysiological and behavioral responses across negative, neutral, and positive stimuli.ResultsAfter 8 weeks, the Tai Chi group exhibited significantly shorter reaction times compared to the control group (p < 0.001), with improvements evident only in the exercise group over time. ERP analyses revealed that Tai Chi training selectively reduced N2 amplitudes to negative stimuli, suggesting decreased early sensitivity to negative information. Additionally, the Tai Chi group showed overall shorter N2 latencies compared to the control group, indicating faster early-stage neural processing. In contrast, P3 amplitudes increased across all valence conditions in the exercise group, reflecting enhanced allocation of attentional resources during later cognitive processing. No significant effects were observed for P3 latency.ConclusionThis study demonstrates that 8 weeks of Tai Chi training modulated both neural and behavioral responses to emotional stimuli in healthy female college students, suggesting potential benefits for attentional processes in emotional regulation, though neural-behavioral links require further investigation.